Cognitive phenotypes and factors associated with cognitive decline in a cohort of older patients with atrial fibrillation: The Strat‐AF study. (5th February 2023) - Salvadori, Emilia; Barucci, Eleonora; Barbato, Carmen; Formelli, Benedetta; Cesari, Francesca; Chiti, Stefano; Diciotti, Stefano; Giusti, Betti; Gori, Anna Maria; Marzi, Chiara; Pescini, Francesca; Pracucci, Giovanni; et al.
Abstract: Background and purpose: The multifactorial relationship between atrial fibrillation (AF) and cognitive impairment needs to be elucidated. The aim of this study was to assess, in AF patients on oral anticoagulants (OACs), the prevalence of cognitive impairment, defined according to clinical criteria or data‐driven phenotypes, the prevalence of cognitive worsening, and factors associated with cognitive outcomes. Methods: The observational prospective Strat‐AF study enrolled AF patients aged ≥ 65 years who were receiving OACs. The baseline and 18‐month protocol included clinical, functional, and cognitive assessment, and brain magnetic resonance imaging. Cognitive outcomes were: empirically derived cognitive phenotypes; clinical diagnosis of cognitive impairment; and longitudinal cognitive worsening. Results: Out of 182 patients (mean age 77.7 ± 6.7 years, 63% males), 82 (45%) received a cognitive impairment diagnosis, which was associated with lower education level and functional status, and higher level of atrophy. Cluster analysis identified three cognitive profiles: dysexecutive (17%); amnestic (25%); and normal (58%). Compared to the normal group, the dysexecutive group was older, and had higher CHA2 DS2 ‐VASc scores, while the amnestic group had worse cognitive and functional abilities, and medial temporal lobe atrophy (MTA). Out of 128 followed‐up patients, 35 (27%) had cognitive worsening that was associated with lower education level, worse cognitive efficiency, CHA2 DS2 ‐VASc score, timing of OAC intake, history of stroke, diabetes, non‐lacunar infarcts, white matter hyperintensities and MTA. In multivariate models, belonging to the dysexecutive or amnestic group was a main predictor of cognitive worsening. Conclusions: In our cohort of older AF patients, CHA2 DS2 ‐VASc score, timing of OAC intake, and history of stroke influenced presence, type and progression of cognitive impairment. Empirically derived cognitive classification identified three groups with different clinical profiles and better predictive ability for cognitive worsening compared to conventional clinical diagnosis.